2022
DOI: 10.5539/jps.v11n1p31
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Adaptation of Eurya japonica Thunb. (Pentaphylacaceae) in Coastal Area

Abstract: To clarify the process of plant adaptation to coastal areas, we conducted morphological and anatomical analyses of Eurya japonica Thunb. (Pentaphylacaceae). There was no significant difference in leaf shape between the inland and coastal populations, although the leaves in coastal populations tended to be thicker. However, our anatomical analysis revealed significant differences in stomatal size and adaxial and abaxial epidermal cell sizes. The smaller stomata of the coastal population of this species were eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The biodiversity of coastal environments is valuable at the global scale, as these environments have high endemism rates of plant species that occur as a result of the unique environments, with strong persistence of shore winds carrying sand and salt spray that dries leaves and soil (Hassani et al, 2021;Nakajima & Yoshizaki, 2018). Plant species in coastal areas have traits adapted to coastal environments (Kumekawa et al, 2013;Ohga et al, 2013;Shiba et al, 2022;Sunami et al, 2013;Takizawa et al, 2022;Tunala et al, 2012); therefore, the conservation and sustainable use of coastal forests require close attention (Cori, 1999;Schlacher et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The biodiversity of coastal environments is valuable at the global scale, as these environments have high endemism rates of plant species that occur as a result of the unique environments, with strong persistence of shore winds carrying sand and salt spray that dries leaves and soil (Hassani et al, 2021;Nakajima & Yoshizaki, 2018). Plant species in coastal areas have traits adapted to coastal environments (Kumekawa et al, 2013;Ohga et al, 2013;Shiba et al, 2022;Sunami et al, 2013;Takizawa et al, 2022;Tunala et al, 2012); therefore, the conservation and sustainable use of coastal forests require close attention (Cori, 1999;Schlacher et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…japonica (Regel) H. Hara (Campanulaceae) has evolved relatively thick leaves via a heterochronic process to store water. Shiba et al (2022b) indicated that the coastal population of Eurya japonica Thunb. (Ternstroemiaceae) had smaller stomata and larger epidermal cells on the adaxial and abaxial sides to reduce transpiration during gas exchange and to retain water in the leaves, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…japonica (Regel) H. Hara (Campanulaceae) had evolved relatively thick leaves via a heterochronic process to store water. Shiba et al (2022) pointed out that coastal populations of Eurya japonica Thunb. (Ternstroemiaceae) have small stomata and larger adaxial and abaxial epidermal cells to reduce transpiration during gas exchange and retain moisture within the leaves.…”
mentioning
confidence: 99%
“…Wind is a particularly complex environmental factor that has several effects on plants (Ennos, 1997). Wind speeds are stronger in coastal areas than inland areas, and wind-induced stress plays an important role in the speciation of plants adapted to coastal areas (Shiba et al, 2022;Takizawa et al, 2022;Takizawa et al, 2023). However, limited studies have been conducted on plant adaptation to wind-induced mechanical stress in coastal areas.…”
mentioning
confidence: 99%